Asymmetric Cu(I)─W Dual‐Atomic Sites Enable C─C Coupling for Selective Photocatalytic CO2 Reduction to C2H4 - Yuyin Mao; Minghui Zhang; Guangyao Zhai; Shenghe Si; Dong Liu; Kepeng Song; Yuanyuan Liu; Zeyan Wang; Zhaoke Zheng; Peng Wang; Ying Dai; Hefeng Cheng; et al. (Advanced Science, 2024)
Abstract Solar‐driven CO2 reduction into value‐added C2+ chemical fuels, such as C2H4, is promising in meeting the carbon‐neutral future, yet the performance is usually hindered by the high energy barrier of the C─C coupling process. Here, an efficient and stabilized Cu(I) single atoms‐modified W18O49 nanowires (Cu1/W18O49) photocatalyst with asymmetric Cu─W dual sites is reported for selective photocatalytic CO2 reduction to C2H4. The interconversion between W(V) and W(VI) in W18O49 ensures the stability of Cu(I) during the photocatalytic process. Under light irradiation, the optimal Cu1/W18O49 (3.6‐Cu1/W18O49) catalyst exhibits concurrent high activity and selectivity toward C2H4 production, reaching a corresponding yield rate of 4.9 µmol g−1 h−1 and selectivity as high as 72.8%, respectively. Combined in situ spectroscopies and computational calculations reveal that Cu(I) single atoms stabilize the *CO intermediate, and the asymmetric Cu─W dual sites effectively reduce the energy barrier for the C─C coupling of two neighboring CO intermediates, enabling the highly selective C2H4 generation from CO2 photoreduction. This work demonstrates leveraging stabilized atomically‐dispersed Cu(I) in asymmetric dual‐sites for selective CO2‐to‐C2H4 conversion and can provide new insight into photocatalytic CO2 reduction to other targeted C2+ products through rational construction of active sites for C─C coupling.